DIGITALIZATION AS A MSME MARKET INTEGRATION DEVELOPMENT SERVICE (STUDY IN PATAAN VILLAGE, SAMBENG DISTRICT, LAMONGAN REGENCY) - Nurul Badriyah; Mochammad Afif; Titin Titin; Rivatul Ridho (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The development of digitalization technology needs to be utilized by the public to increase productivity both in terms of production and marketing. Efforts to assist the digitalization of technology and the integration of MSME actors can increase market expansion and overall digital application knowledge. The community empowerment effort is used for digitization for market development techniques for the distribution of production and promotion of local products. The methods used in the empowerment process are mapping, data collection and Forum Group Discussion (FGD). As well as making the application center for MSME products. The result of the empowerment is the emergence of 25 food versions of MSME products that are included in the pataan store application, it is hoped that MSME actors will be able to operate digital systems to facilitate the marketing concept of online product distribution.